RELATIONSHIPS AMONG INTERNET ADDICTION, ACADEMIC PROCRASTINATION AND ACADEMIC ACHIEVEMENT IN ADOLESCENTS - Yasin DEMİR (Fırat University, 2019)
The aim of this study is to examine the relationships among internet addiction, academic procrastination and academic success in adolescents. The research was conducted on adolescents studying in high school in Malatya province. In this context, ethics committee approval was first obtained from Inonu University. Later, written consent was obtained from the Malatya governorship. After obtaining ethical and legal permits, data were collected from high school students who are internet users and voluntary adolescents. The research data were collected with the Young Internet Addiction Test-Short Form (YIBT-KF), Academic Procrastination Scale and personal information form. In the analysis of the data, SPSS-18 and AMOS package programs were used. In the analysis of the data, frequency, percentage, t test, anova, correlation analysis and structural equation modeling were used. t test results showed that internet addiction and academic procrastination behaviors did not differ according to sex. Academic achievement scores were found significantly different in favor of females. Adolescents using smartphones have significantly higher levels of internet addiction as well as academic procrastination behaviors. The difference between academic achievement scores and having a smartphone is not significant. It has been found that there are significant differences among internet dependency, academic procrastination, academic achievement scores, and average daily internet use time. There is a positive relationship between Internet addiction and academic postponement, but a negative relationship between academic success. It has been found that there is a negative correlation between academic success and academic achievement. Internet addiction affects academic procrastination positively. The academic procrastination negatively affects academic achievement. When the model is examined as a whole, as the internet addiction increases, the academic procrastination increases and as the academic procrastination increases, the academic achievement decreases, in adolescents.